2006
DOI: 10.1088/0953-2048/19/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aromatic hydrocarbon addition onin situpowder-in-tube processed MgB2tapes

Abstract: We fabricated in situ powder-in-tube processed MgB 2 /Fe tapes using aromatic hydrocarbon of benzene, naphthalene, and thiophene as additives, and investigated the superconducting properties. We found that these aromatic hydrocarbons were very effective for increasing the Jc values. The Jc values of 20mol% benzene-added tapes reached 130A/mm 2 at 4.2K and 10T. This value was almost comparable to that of 10mol% SiC -added tapes and about four times higher than that of tapes with no additions.Microstructure anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 11 publications
4
102
1
3
Order By: Relevance
“…2 These record high properties have been confirmed and reproduced by many groups, 2,5,10,11 and the performance records remain unbroken up to now. However, the best high-field J c values achieved in the SiC doped MgB 2 wires were compromised by the reduction in self-field and low-field J c .…”
mentioning
confidence: 55%
“…2 These record high properties have been confirmed and reproduced by many groups, 2,5,10,11 and the performance records remain unbroken up to now. However, the best high-field J c values achieved in the SiC doped MgB 2 wires were compromised by the reduction in self-field and low-field J c .…”
mentioning
confidence: 55%
“…The research toward improvement of j c properties in MgB 2 has been mostly aimed at enhancing the H irr , the flux pinning ability, and H c2 by irradiation or chemical doping. [2][3][4][5][6][7][8] Chemical doping has been proved to be a simple and effective way to introduce pinning centers into MgB 2 superconductor or to improve the upper critical field. It is believed that carbon containing dopants, such as nano-SiC, 5 carbon nanotubes, 6 nanocarbon, 7 hydrocarbons, 8 silicone oil, 9,10 malic acid, 11 etc., are especially effective in enhancing the H c2 , and hence the j c properties of MgB 2 in high magnetic fields.…”
Section: Introductionmentioning
confidence: 99%
“…19 such as silicone oil and other oxide or nonoxide nanomaterials. [5][6][7][8][9][10][11]19,20 Improvement of the j c ͑B͒ was quite successful for most of chemical doped MgB 2 . However, the origin of the pinning mechanisms are still not well understood except the silicon oil doped case.…”
Section: Introductionmentioning
confidence: 99%
“…Although Yamada et al 14 prepared Fe sheathed tape samples by using a liquid aromatic hydrocarbon together with ball milling, it is very difficult to control the composition during ball milling because of its volatile properties. In this study, therefore, we suggested a different hydrocarbon, pyrene ͑C 16 H 10 ͒, which has no oxygen content, as the C source.…”
mentioning
confidence: 99%